2021
DOI: 10.3390/genes12081220
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Genotypic Spectrum of Scoliosis in Multiple Pterygium Syndrome: A Case Series on 12 Children

Abstract: Background: Multiple pterygium syndrome (MPS) is a genetically heterogeneous rare form of arthrogryposis multiplex congenita characterized by joint contractures and webbing or pterygia, as well as distinctive facial features related to diminished fetal movement. It is divided into prenatally lethal (LMPS, MIM253290) and nonlethal (Escobar variant MPS, MIM 265000) types. Developmental spine deformities are common, may present early and progress rapidly, requiring regular fo llow-up and orthopedic management. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the literature, five patients were described with a heterozygous compound mutation causing Escobar syndrome [ 13 , 15 ]. Other studies suggested the presence of variants in the regulatory intronic regions in Escobar patients given their absence in exons and other genes associated with this pathology, such as CHRNA1 , CHRND, TPM2, and MYH3 [ 4 , 38 , 39 ]. Other studies, could not associate the phenotype with any particular related genetic variant…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, five patients were described with a heterozygous compound mutation causing Escobar syndrome [ 13 , 15 ]. Other studies suggested the presence of variants in the regulatory intronic regions in Escobar patients given their absence in exons and other genes associated with this pathology, such as CHRNA1 , CHRND, TPM2, and MYH3 [ 4 , 38 , 39 ]. Other studies, could not associate the phenotype with any particular related genetic variant…”
Section: Discussionmentioning
confidence: 99%
“…Patients with this disorder often exhibit significant scoliosis and limited mobility. To date, only six studies with less than 20 patients involving with CPSF1B have been reported (Cameron‐Christie et al., 2018 ; Dahan‐Oliel et al., 2021 ; Hakonen et al., 2020 ; Kamien et al., 2022 ; Thiffault et al., 2019 ; Zhao et al., 2022 ), which keeps the characteristic spectrum, natural clinical course, and pathogenesis of this disease still far from well‐known.…”
Section: Introductionmentioning
confidence: 99%
“…Further research using genomics and animal models to identify prognostic factors and therapeutic targets for AMC needs to be implemented. Dahan et al [ 10 ] described the clinical and genetic heterogeneity in patients with multiple pterygium syndrome and scoliosis, harboring mutations in CHNRG and MYH3 .…”
Section: Introductionmentioning
confidence: 99%